1972
DOI: 10.2466/pr0.1972.31.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the People Concept in Pigeons

Abstract: The present investigation sought to determine the minimal number of positive and negative examples of a complex concept necessary for criterion mastery. A complex concept was defined as one in which the stimulus properties are not easily specified by physical measurement. Ss were presented with a stimulus display containing pictures of people and pictures where people were absent. Responses to pictures of people were reinforced with food. The results indicated that (1) pigeons rapidly form a complex concept wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Poole and Lander (1971) demonstrated that pigeons could learn to discriminate between pictures of different breeds of pigeons, other animals, and nonliving objects. Malott and Siddall (1972) used pictures of people, and Cerelia (1979) reported that pigeons could learn to discriminate between oak leaves and could respond to 40 new stimuli without a discrimination decrement. In related studies.…”
Section: Discussionmentioning
confidence: 99%
“…Poole and Lander (1971) demonstrated that pigeons could learn to discriminate between pictures of different breeds of pigeons, other animals, and nonliving objects. Malott and Siddall (1972) used pictures of people, and Cerelia (1979) reported that pigeons could learn to discriminate between oak leaves and could respond to 40 new stimuli without a discrimination decrement. In related studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, the grannnatical child will not be able to state the rules of grannnar. This is like the pigeon that cannot state the rules describing the concepts of human being and nonhuman being, though the bird's key peck is under the differential control of those stimulus classes (Hermstein & Loveland, 1964;Malott & Siddall, 1972).…”
Section: Rule-governance Vs Behavioral Consistencymentioning
confidence: 99%
“…To investigate the establishment of perceptual classes, most researchers have used simple discrimination training procedures in which many stimuli are drawn from two or more potential classes (e.g., Bhatt et al, 1988;Cook et al, 1990;Engelmann & Carnine, 1982;Herrnstein, 1990;Herrnstein, Loveland, & Cable, 1976;Honig & Stewart, 1988;Lubow, 1974;Malott & Siddall, 1972;Porter & Neuringer, 1985;Wasserman et al, 1988). In contrast, conditional discrimination training procedures have been used by a smaller number of researchers to investigate the establishment of perceptual classes.…”
mentioning
confidence: 99%